Buddhist Philosophy of Language in India : Jñānaśrīmitra on Exclusion - Suchartkullawit, Oraphan (วารสารสันติศึกษาปริทรรศน์ มจร, 2019)
“Buddhist Philosophy of Language in India : Jñānaśrīmitra on Exclusion” เขียนโดย Lawrence J. McCrea, and Parimal G. Patil